Intercultural Sensitivity of Teachers in a Culturally Heterogeneous Context in Serbia: Accepting Cultural Differences or Overrating One’s Intercultural Sensitivity? - Dimitrijević, Bojana; Petrović, Danijela; Zlatković, Blagica; Starčević, Jelena (Studies in Teaching and Education, 2024)
The subject of this article is intercultural sensitivity of teachers in a culturally heterogeneous context in Serbia, defined in accordance with the Developmental Model of Intercultural Sensitivity of Milton Bennett. The main objective of this research was to determine the following: a) average developmental orientation and perceived orientation scores of the teachers; b) frequency of participants in different stages of developmental orientation; c) whether there are significant differences between the developmental and the perceived orientation of teachers; d) whether the gap between the perceived and the developmental orientation varies across the developmental continuum in line with the supposition of the Dunning–Kruger effect. The sample consisted of 76 elementary school teachers from Vojvodina and South Serbia. Furthermore, the Intercultural Development Inventory (IDI®), used in this research, is based on the theoretical foundations of the selected model of intercultural sensitivity. The results indicate that the mean developmental orientation of teachers is in the range of minimization, while they perceive themselves as more interculturally sensitive, in alignment with the ethno-relativistic orientation of acceptance. Differences between the perceived and the developmental orientation are significant. The gap between the perceived and the developmental orientation decreases with higher intercultural sensitivity, meaning that those teachers who are interculturally sensitive are more objective in assessing their own intercultural sensitivity in comparison with those who are less interculturally sensitive. Implications of the obtained results, when it comes to the professional roles of teachers and their development as reflexive practitioners, are further discussed in this article.
Keywords: Developmental Model of Intercultural Sensitivity; Teachers; Intercultural Development Inventory – IDI®; Developmental and Perceived Orientation; Dunning–Kruger effect